Implementasi Penggunaan SISKEUDES dan Pembukuan PDAM Melalui Program KKN-T di Desa Baskara Bakti - Eni Karsiningsih; Hasanah Eka Risti; Salwazeela Septiani; Muhammad Aldi Irfan; Odi Al Ashafani; Giberto Vero; Jurdi Pratama (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
KKN-Thematic (Real Work Lecture) is a form of student service to the community as part of the tridharma of higher education. This program aims to support village development and provide students with the opportunity to practice the knowledge they have learned directly. The purpose of this program is to identify challenges and opportunities in aligning the village financial management system to be more effective. A case study approach is used to analyze the implementation process and collect data on the integration efforts. Some of the problems faced by Baskara Bakti Village include data compatibility, limited technical capacity, and information gaps between SISKEUDES and PDAM. This service activity underlines the importance of strengthening institutional coordination, increasing technical support, and developing standard data formats to facilitate smooth integration in SISKEUDES. By addressing these challenges, villages can optimize financial management practices and improve the provision of public services.